Pemertahanan Bahasa Batak Toba di Desa Narumonda Vii Kecamatan Siantar Narumonda Kabupaten Toba - David Kristopani Marpaung; Flansius Tampubolon (Journal of Language Development and Linguistics, 2022)
This study discusses the preservation of the Toba Batak language in Narumonda VII Village, Siantar Narumonda District, Toba Regency. The problem studied is the preservation of the Toba Batak language in Narumonda VII Village based on its bilingual pattern and the attitude of the Toba ethnic community in maintaining their language. The background of this research is to see the role of the use of the Toba Batak language as a regional language and Indonesian as the national language in an area where the majority of the population is Toba Batak ethnicity.The method used in collecting data is the conversational method to-face and followed by the note-taking technique. Data was obtained by distributing questionnaires to respondents. This research data assessment method uses quantitative methods. The data were analyzed using sociolinguistic theory. From the results of the study, it can be concluded that the pattern of using the Toba Batak language at the age of over 20 years (adults) is still high compared to the use of the Toba Batak language at the age of under 20 years. At the age of 20 years and over, Toba Batak language users showed positive language attitudes (85%), while those under 20 years old showed negative language attitudes (10.5%).